The Impact of Product Quality, Service Quality, and Perceived Value on Customer Satisfaction: Evidence from a Coffee Shop in Indonesia - Rahmi, Raissa Aristawati; Munawaroh, Munjiati (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The rapid growth of the coffee shop industry in Indonesia has intensified competition among businesses, making customer satisfaction an important factor for maintaining competitiveness and business sustainability. This study aims to examine the influence of product quality, service quality, and perceived value on customer satisfaction at Kopi Gunung Coffee Shop in Cilacap, Indonesia. A quantitative research approach was employed, and primary data were collected through questionnaires distributed to customers of Kopi Gunung Coffee Shop. Using purposive sampling, a total of 202 valid responses were obtained from customers who had visited the coffee shop at least twice. The data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results indicate that product quality has a positive and significant effect on customer satisfaction. Similarly, service quality and perceived value also have positive and significant influences on customer satisfaction. These findings suggest that improving product quality, delivering excellent service, and providing good value to customers are essential strategies for enhancing customer satisfaction in the coffee shop industry. The study contributes to the marketing literature by providing empirical evidence on the determinants of customer satisfaction in the food and beverage sector, particularly in the context of local coffee shop businesses.